Retrograde Ascending Dissection After Thoracic Endovascular Aortic Repair Combined With the Chimney Technique and Successful Open Repair Using the Frozen Elephant Trunk Technique. (January 2018) - Hirano, Koji; Tokui, Toshiya; Nakamura, Bun; Inoue, Ryosai; Inagaki, Masahiro; Maze, Yasumi; Kato, Noriyuki
The chimney technique can be combined with thoracic endovascular aortic repair (TEVAR) to both obtain an appropriate landing zone and maintain blood flow of the arch vessels. However, surgical repair becomes more complicated if retrograde type A aortic dissection occurs after TEVAR with the chimney technique. We herein report a case involving a 73-year-old woman who developed a retrograde ascending dissection 3 months after TEVAR for acute type B aortic dissection. To ensure an adequate proximal sealing distance, the proximal edge of the stent graft was located at the zone 2 level and an additional bare stent was placed at the left subclavian artery (the chimney technique) at the time of TEVAR. Enhanced computed tomography revealed an aortic dissection involving the ascending aorta and aortic arch. Surgical aortic repair using the frozen elephant trunk technique was urgently performed. The patient survived without stroke, paraplegia, renal failure, or other major complications. Retrograde ascending dissection can occur after TEVAR combined with the chimney technique. The frozen elephant trunk technique is useful for surgical repair in such complicated cases.